The effect of sodium glucose Co-transport 2 inhibitors on cognitive impairment and depression in type 2 diabetes mellitus patients - Ashurova Nodirahon; Haya Majid; Swati Waghdhare; Divya Vohora; Nidhi (Elsevier, 2024)
Background and aim: Type 2 diabetes mellitus (T2DM) is a prevalent metabolic disorder often associated with thyroid dysfunction. Sodium-glucose co-transport 2 (SGLT2) inhibitors, a novel class of medications for T2DM, have shown potential effects on various physiological systems, including the central nervous system (CNS). This study aimed to investigate the impact of SGLT2 inhibitors on cognition and depression in T2DM patients and its potential association with thyroid dysfunction. Methods: A case-control observational study was conducted involving 138 participants, including T2DM cases and healthy controls. Data on demographics, anthropometric measures, metabolic parameters, thyroid function, depression (Physical Health questionnaire- 9), and cognition (Montreal Cognitive Assessment questionnaire) were collected. Subgroup analysis compared different SGLT2 inhibitors. Results: T2DM patients taking SGLT2 inhibitors exhibited significantly higher levels of thyroid-stimulating hormone (TSH) compared to controls (p < 0.001). Additionally, T2DM patients on SGLT2 inhibitors showed a higher prevalence of mild to moderate depression (p < 0.001, odds ratio = 1.74) and cognitive impairment (p = 0.039, odds ratio = 1.32) compared to controls. Subgroup analysis revealed varying effects among different SGLT2 inhibitors on depression and cognitive function. Conclusion: SGLT2 inhibitors in T2DM patients may have unexpected consequences on thyroid function, depression, and cognition. These findings highlight the need for comprehensive patient care, including mental health assessment, when prescribing SGLT2 inhibitors. Further research is warranted to elucidate the underlying mechanisms and optimize the management of T2DM patients using these medications.